Dually Active Polycation/miRNA Nanoparticles for the Treatment of Fibrosis in Alcohol-Associated Liver Disease - Chuhan Zhang; Yu Hang; Weimin Tang; Diptesh Sil; Heather C. Jensen-Smith; Robert G. Bennett; Benita L. McVicker; David Oupický (MDPI AG, 2022)
Alcohol-associated liver disease (AALD) is a major cause of liver disorders worldwide. Current treatment options are limited, especially for AALD-associated fibrosis. Promising approaches include RNA interference for miR-155 overexpression in Kupffer cells (KCs), as well as the use of CXCR4 antagonists that inhibit the activation of hepatic stellate cells (HSCs) through the CXCL12/CXCR4 axis. The development of dual-functioning nanoparticles for the effective delivery of antifibrotic RNA together with a CXCR4 inhibitor thus promises to improve the treatment of AALD fibrosis. In this study, cholesterol-modified polymeric CXCR4 inhibitor (Chol-PCX) was synthesized and used to encapsulate anti-miR-155 or non-coding (NC) miRNA in the form of Chol-PCX/miRNA nanoparticles. The results indicate that the nanoparticles induce a significant miR-155 silencing effect both in vitro and in vivo. Treatment with the Chol-PCX/anti-miR-155 particles in a model of moderate alcohol consumption with secondary liver insult resulted in a significant reduction in aminotransferase enzymes as well as collagen content in the liver parenchyma. Overall, our data support the use of Chol-PCX as a carrier for anti-miR-155 for the combined therapeutic inhibition of CXCR4 and miR-155 expression as a way to improve fibrotic damage in the liver.